Development of regional economic infrastructure based on innovation - Abylkassimova, Zh.A.; Gumurzakova, L.S.; Akisheva, D.M.; Sarzhanov, D.K.; Amangeldiyeva, Zh.A. (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of this article is to consider the development of regional innovation activity: principles, objectives, operational elements, and approaches to managing the development of innovation activity at the regional level. Methods: The research uses methods of statistical analysis, comparative analysis, and graphs. Findings: The key results of the study are summarized in the following conclusions: 1) The study examines the main factors of competitiveness, their impact, and relevance to increasing competitiveness in the regional socio-economic system. 2) The study shows that the region has difficulty accepting and developing innovations and that the level of innovation is not yet at the proper level. 3) It was presented that innovation and logistics have a huge impact on the competitiveness of the region. 4) The growth rates of the number of innovative products and the growth rates of the share of large and medium-sized companies using digital technologies in the industry have been determined. Conclusions: A detailed description of innovations in the region makes it possible to compare the levels of development of the innovation sphere in the region. The detection of the dependence of the subjects of economic relations on the conditions proposed in the study makes it possible to establish the characteristics of innovative interaction together with the external and internal components of the innovation process of the regional economy.